Comprehensive analysis of antimicrobial resistance in the Southwest Indian Ocean: focus on WHO critical and high priority pathogens - Axel O. G. Hoarau; Patrick Mavingui; Guillaume Miltgen; Guillaume Miltgen; Guillaume Miltgen (Frontiers Media S.A., 2024)
The spread of antimicrobial resistance (AMR) is a major global concern, and the islands of the Southwest Indian Ocean (SWIO) are not exempt from this phenomenon. As strategic crossroads between Southern Africa and the Indian subcontinent, these islands are constantly threatened by the importation of multidrug-resistant bacteria from these regions. In this systematic review, our aim was to assess the epidemiological situation of AMR in humans in the SWIO islands, focusing on bacterial species listed as priority by the World Health Organization. Specifically, we examined Enterobacterales, Acinetobacter spp., Pseudomonas spp. resistant to carbapenems, and Enterococcus spp. resistant to vancomycin. Our main objectives were to map the distribution of these resistant bacteria in the SWIO islands and identify the genes involved in their resistance mechanisms. We conducted literature review focusing on Comoros, Madagascar, Maldives, Mauritius, Mayotte, Reunion Island, Seychelles, Sri Lanka, and Zanzibar. Our findings revealed a growing interest in the investigation of these pathogens and provided evidence of their active circulation in many of the territories investigated. However, we also identified disparities in terms of data availability between the targeted bacteria and among the different territories, emphasizing the need to strengthen collaborative efforts to establish an efficient regional surveillance network.